Studying the Prevalence of Psoriasis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Psoriasis is characterized by the presence of two peaks of incidence and, in accordance with this, two types of dermatosis: The first type is characterized by a hereditary predisposition and early onset of the disease (usually at 15-25 years), the second type is characterized by a late onset of the disease (after 40 years) and the absence of genetic predisposition [2, 3, 5, 8, 11]. A large amount of data has been accumulated on the presence of an association of type 1 psoriasis with hla antigens of classes I and II [4, 10, 12, 13, 15]. 8 loci have been identified to date predisposition to psoriasis, which mapped on 8 chromosomes and designated psors1—psors8. it was established that the locus psors1, located on the short arm of the 6th chromosomes (6p21.3), is the main one, because it contains several linked genes actively expressed in skin keratinocytes. This locus represents the area in which there are five genes [hla-c, tcf19(sc1), otf3 (pouf5f1), hcr(pg8), cdsn], from of which two (hcr u cdsn) have an association with psoriasis [6, 11—15]. However with what type psoriasis, these genes are associated is not clear, which determined the need to carry out of this study.